Grape seed oil in the diet of primiparous Jersey cows before and after parturition: effects on performance, health, rumen environment, and milk quality - Signor M.H.* (2024)
© The Author(s), under exclusive licence to Springer Nature B.V. 2024.The objective of the study was to determine whether adding grape seed oil (GSO) to the diet of primiparous Jersey breeds during the transition period would improve animal health by measuring effects on the rumen environment, serum biochemistry, oxidative response, and the composition and quality of milk. We used 14 Jersey heifers, weighing an average of 430 kg and 240 days of gestation. The animals were divided into two groups and offered a basal diet, including GSO in the concentrate for the GSO group (dose of 25 mL per animal day) and the same dose of soybean oil (SO) for the control group. The animals were allocated and maintained in a compost barn system, receiving an anionic diet (pre-partum) and a diet for postpartum lactating animals. Dry matter intake (DMI), milk production, serum biochemistry, serum and milk oxidative stability, ruminal fluid and milk fatty acid profile, milk qualitative aspects, and ruminal parameters such as pH, bacterial activity, and protozoan count were evaluated. The addition of GSO had a positive effect on the health of the cows, especially on the oxidative stability of the cows, by increasing total thiols (P = 0.03), higher plasma ferric reducing capacity (FRAP) (P = 0.01), and total antioxidant capacity (TAC) (P = 0.01). In the oxidative stability of the milk produced by the treated animals, there was also an increase in TAC (P = 0.05) and FRAP (P = 0.03). Discreet changes were observed in the ruminal environment with a decreasing trend in pH (P = 0.04) but an increase in bacterial activity (P = 0.05) and protozoa counts (P = 0.07) in cows that consumed the additive. GSO consumption affected the fatty acid profile in milk, increasing saturated fatty acids (SFA) (P = 0.05) and reducing unsaturated fatty acids (UFA) (P = 0.03). The oil did not affect milk production or efficiency in the postpartum period. Based on this information, it is concluded that the addition of GSO positively affects the cow's antioxidant system.